Optimization of combined thermal power plant and performance analysis using matlab/simulink using real data: Kuwait as a case study - Alshammari, Meshari F A F; Toha, Siti Fauziah; Anuar, Hazleen; Buys, Yose Fachmi (AlamBiblio Publishers, 2021)
To increase the overall plant efficiency, the Combined cycle power plant (CCPP), which is a combination of the Gas turbine (Brayton cycle) and steam turbine (Rankine cycle), is a highly efficient system for electricity generation. In this paper, optimization and performance simulation analysis of Subiyah Combined Thermal Power Plant using real operating data is performed. The model is developed usingMATLAB software. The main factors in the top and bottom cycles of the combined cycle are investigated and discussed. The simulation results demonstrate the exhaust of the Gas turbine reached up to 600°C. The net-power output based on the performance model using MATLAB (Simulink) is greater than the station's current real output by 20.5%. The overall thermal efficiency of the power plant is also raised from 50.5% to 55.2%.